Femtosecond laser induced periodic surface structures on hydrogenated amorphous silicon thin films - Almeida, G. F.B.; Cardoso, M. R.; Constantino, C. J.L. [UNESP]; Aoki, P. H.B. [UNESP]; Rodrigues, C. A.; Lima, J. J.D.; Costa, L. da F.; Mendonça, C. R. (Optica Publishing Group, 2013)
We report a study of fs-laser micromachining on the structure and surface morphology of hydrogenated amorphous silicon thin films using Raman spectroscopy and scanning electron and atomic force microscopy. © OSA 2013.